METHODOLOGICAL ASPECTS OF IMPROVING THE PERFORMANCE OF LOGISTICS ORGANIZATIONS - O. S. Dyakonova (Publishing House of the State University of Management, 2020)
The methodological aspects of the performance of logistics organizations have been revealed. The generalizing performance indicators of logistics have been given. The scientific approaches to the assessment of the ability of the enterprise to work effectively have been considered. The analysis of indicators of public financial statements of some logistics companies has showed that the main problems of reducing the efficiency of their work are associated with low profitability and slow turnover of invested capital. Therefore, the evaluation of the economic performance of logistics organizations should be expanded and supplemented by specific indicators of resource efficiency, which take into account certain aspects of their work. In the process of evaluating the effectiveness of logistics enterprises should be taken into account both indicators characterizing the logistics system itself, and indicators characterizing the operation of the system.